The Viral Loop - a Straight Path to Sustainable User Growth?: A Case Study of a Global Audio Streaming Company - Paulsson, Daniela; Richnau, Ebba (My University, 2022)
The viral loop is described as an effective way for companies to achieve compounding growth, without incurring any advertisement costs, by engaging users to voluntarily promote a product. We analyzed this concept based on the case of a global audio streaming company. The purpose of this study is to investigate how potential users navigate through the viral loop of an audio streaming company and the reasons behind their behavior, to optimize for sustainable user growth. Our research was designed as a single case study and we collected the data through qualitative semi-structured interviews with users of different audio streaming services. The results suggest that potential users can navigate through the viral loop of audio in various ways. We present a model that provides insights into the fundamental steps that exist in the viral loop of audio. The steps we identified that users could pass through are consuming, sharing, receiving, and opening. In addition, some users might go through the optional steps of previewing content, saving content for later, and reactivating or creating an account. Nonetheless, not all potential users will convert between the different steps of the viral loop. Thus, our study investigates habits, triggers, abilities, motivations, situational constraints, and other factors that might influence user behavior. Based on an analysis of these factors, the viral loop of audio can be optimized by identifying user needs and stimulating the conversion rates between the different steps. In general, the steps that the receiver takes in the viral loop are identified as a potential area of improvement for the audio streaming company. These steps all affect the accept rate of viral invitations. Specifically, we propose that ensuring access to content that is shared and providing methods for consuming saved content later could be beneficial. However, it might be difficult to alter established user habits. Moreover, potential new users consider a multitude of factors and are generally reluctant to sign up for new services. Nevertheless, the engagement, satisfaction, and retention of existing users are other consequences of effective viral loops that could stimulate sustainable user growth over time. Consequently, the viral loop might not provide an entirely straight path for the audio streaming company to achieve sustainable user growth
Keywords: the viral loop; audio streaming; user behavior; sharing, receiving; digital content; user acquisition; sustainable growth